2017
DOI: 10.1111/tpj.13613
|View full text |Cite
|
Sign up to set email alerts
|

WIDE AND THICK GRAIN 1, which encodes an otubain‐like protease with deubiquitination activity, influences grain size and shape in rice

Abstract: Grain size and shape are two crucial traits that influence grain yield and grain appearance in rice. Although several factors that affect grain size have been described in rice, the molecular mechanisms underlying the determination of grain size and shape are still elusive. In this study we report that WIDE AND THICK GRAIN 1 (WTG1) functions as an important factor determining grain size and shape in rice. The wtg1-1 mutant exhibits wide, thick, short and heavy grains and also shows an increased number of grain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(96 citation statements)
references
References 45 publications
1
83
0
1
Order By: Relevance
“…Genes involved in the ubiquitin pathway are also important regulators of grain weight in many plant species, including GW2 (reviewed in Li and Li ). Genes with deubiquitinating activity have also been shown to influence seed size, such as WIDE AND THICK GRAIN 1 ( WTG1 ) in rice and UBIQUITIN SPECIFIC PROTEASE 15 ( UBP15 ) in Arabidopsis , which act as negative and positive regulators of seed size, respectively (Du et al ; Huang et al ). Genes involved with phytohormone signaling are also important regulators of seed size, with roles being demonstrated for auxin, brassinosteroid and cytokinin biosynthesis and signaling components (Riefler et al ; Schruff et al ; Jiang et al ).…”
Section: Mechanistic Control Of Grain Weightmentioning
confidence: 99%
“…Genes involved in the ubiquitin pathway are also important regulators of grain weight in many plant species, including GW2 (reviewed in Li and Li ). Genes with deubiquitinating activity have also been shown to influence seed size, such as WIDE AND THICK GRAIN 1 ( WTG1 ) in rice and UBIQUITIN SPECIFIC PROTEASE 15 ( UBP15 ) in Arabidopsis , which act as negative and positive regulators of seed size, respectively (Du et al ; Huang et al ). Genes involved with phytohormone signaling are also important regulators of seed size, with roles being demonstrated for auxin, brassinosteroid and cytokinin biosynthesis and signaling components (Riefler et al ; Schruff et al ; Jiang et al ).…”
Section: Mechanistic Control Of Grain Weightmentioning
confidence: 99%
“…Studies have also shown that UPS also participates in the control of seed size; for example, GRAIN WIDTH2 (GW2, a RING‐type protein) functions as an E3 ubiquitin ligase for rice expansin‐like 1 in the UPS pathway and negatively regulates grain size and weight (Song et al 2007; Choi et al 2018). WIDE AND THICK GRAIN1 ( WTG1 ) encodes an otubain‐like protease with deubiquitination activity, which determines grain size and shape mainly by influencing cell expansion (Huang et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Second, similar phenotypes were observed in plants with disrupted OsOTUB1 function by CRISPR/Cas9. Third, Huang et al [5] also recently reported the null allele mutant (wtg1) of OsOTUB1 and the same grain phenotypes as OsOTUB1 loss-of-function mutants were observed, further confirming that OsOTUB1 negatively regulates these traits. In contrast, OsOTUB1 overexpression induced aberrant phenotypes such as dwarfism, malformed panicle with decreased grain number, necrotic leaves, and decreased tiller number per plant, which are not completely opposite to the phenotypes of the loss-of-function mutants, and thus, may indicate the side-effect of OsOTUB1 overproduction.…”
mentioning
confidence: 59%